A study on factors that influence the changes of oil price in Malaysia / Wan Nor Saliana Wan Mohd Saleh - Wan Mohd Saleh, Wan Nor Saliana (2011)
This research is conducted to study the factors that influence the changes of oil price in Malaysia. The objectives of this research are to identify the most and least dominant factor that contributes to price of oil and to determine significant relationship between the inflation rate, exchange rate (Malaysia Ringgit To USD) and subsidies provided by the government with the price of oil. Moreover, this study is to determine whether the three independent variables that have been taken as measurements that are inflation rate, exchange rate and subsidies being influenced or not towards the dependent variable that is price of oil in Malaysia. The study done by using the secondary data as sources .The results show that there is some positive relationship between the measurements taken with the changes of oil price in Malaysia